Cuff inflation during ambulatory blood pressure monitoring and heart rate - Mia Skov-Madsen; My Svensson; Jeppe Hagstrup Christensen (Dove Medical Press, 2008)
Mia Skov-Madsen, My Svensson, Jeppe Hagstrup ChristensenDepartment of Nephrology, Aarhus University Hospital, Aalborg, DenmarkIntroduction: Twenty four-hour ambulatory blood pressure monitoring is a clinically validated procedure in evaluation of blood pressure (BP). We hypothesised that the discomfort during cuff inflation would increase the heart rate (HR) measured with 24-h ambulatory BP monitoring compared to a following HR measurement with a 24-h Holter monitor.Methods: The study population (n = 56) were recruited from the outpatient’s clinic at the Department of Nephrology, Aalborg Hospital, Aarhus University Hospital at Aalborg, Denmark. All the patients had chronic kidney disease (CKD). We compared HR measured with a 24-h Holter monitor with a following HR measured by a 24-h ambulatory BP monitoring.Results: We found a highly significant correlation between the HR measured with the Holter monitor and HR measured with 24-h ambulatory blood pressure monitoring (r = 0.77, p < 0.001). Using the Bland-Altman plot, the mean difference in HR was only 0.5 beat/min during 24 hours with acceptable limits of agreement for both high and low HR levels. Dividing the patients into groups according to betablocker treatment, body mass index, age, sex, angiotensin-converting enzyme inhibitor treatment, statins treatment, diuretic treatment, or calcium channel blocker treatment revealed similar results as described above.Conclusion: The results indicate that the discomfort induced by cuff inflation during 24-h ambulatory BP monitoring does not increase HR. Thus, 24-h ambulatory BP monitoring may be a reliable measurement of the BP among people with CKD.Keywords: ambulatory blood pressure monitoring, Holter monitoring, heart rate, chronic kidney disease, hypertension